Comparison of profitability indicators of commercial banks: The case of Malaysia and Pakistan - Al-Behadili, Nooruldeen (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: The main driver of an economy as a whole is a banking system; the government intervenes into the economy by using banking sector, so profitability determinants of the banking system need to be evaluated. The aim of this study is to compare empirically and measure financial performance of commercial banks in Malaysia and Pakistan for the period of 2006-2011. In this paper macroeconomic variables will be used as well as financial ratios which are based on the CAMEL approach. Tufan (2008) and Hamrat (2008) found that foreign banks outperform domestic ones. To evaluate empirically most commonly used ratios will be employed in this study. Two profitability determinants are used as dependent variables. Furthermore data is checked for robustness of the model and OLS methodology is applied by adopting Eviews program. For this purpose, many banking literatures were studied to form an appropriate model. Keywords: Commercial Banks, Malaysia, Pakistan, CAMEL Approachiv. ………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Ekonominin ana sürücüsü bütünüyle banka sistemidir, devlet ekonomiye banka sektörünü kullanarak müdahale eder, bu yüzden banka sisteminin karlılık belirleyicileri değerlendirilmelidir. Bu çalışmanın amacı Malezya ve Pakistan„da 2006 – 2011 yılları arasındaki finansal performansları deneysel olarak karşılaştırmak ve ölçmektir. Bu çalışmada makroekonomik çeşitlilik ve ayrıca finansal ölçülerin bağlı olduğu CAMEL yaklaşımı kullanılacaktır. Tufan (2008) ve Hamrat (2008) yabancı bankaların yerli bankalardan daha iyi performans gösterdiğini bulmuştur. Bu çalışmada deneysel olarak değerlendirebilmek için genel olarak kullanılan ölçütler istihdam edilecektir. Ayrıca veri modelinin sağlamlığı kontrol edilecek ve OLS yöntemi Eviews program kullanılarak uygulanacaktır. Bu amaçla uygun bir model oluşturmak için bankacılık literatürü araştırılacaktır. Anahtar Kelimeler: Ticari Bankalar, Malezya, Pakistan, CAMEL Yaklaşım.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2013. Supervisor: Assoc. Prof. Dr. Nesrin Özataç.
Keywords: Banking and Finance; Banks and Banking - Malaysia; Commercial Banking - Malaysia; Commercial Banks Malaysia Pakistan AMEL Approach